Factors Contributing to the Erosion of Freehand Sketching Competence in Technology Education: A Case Study of Bayero University, Kano - Yusuf M. YAHAYA (FUDMA Journal of Engineering and Technology, 2025)
Many undergraduate students in the Department of Technology Education at Bayero University, Kano, exhibit reluctance toward answering sketch-based questions, potentially hindering their engagement and understanding in subjects requiring visual representation. This study explores the underlying causes of this trend, focusing on factors such as self-perceived confidence in sketching abilities, clarity of instructional guidance, perceived relevance to learning outcomes, and fear of peer or instructor judgment. A structured survey questionnaire was administered to 147 technology education undergraduates using a random sampling method. The study reveals that insufficient practice, time constraints, and inadequate instructional support are the primary contributors to declining sketching proficiency. Findings suggest that integrating regular hand sketching exercises into the curriculum, providing timely and constructive feedback, and fostering an encouraging classroom environment can enhance students’ willingness to engage visually. These interventions may ultimately improve both academic performance and creative problem-solving skills in technology-related disciplines. The study emphasises the importance of reinforcing foundational visual communication skills in contemporary technology education programs.
Keywords: Freehand sketch, competence, technology, education, visual communication.